BT resin-based composite dielectric material for IC (integrated circuit) chip packaging carrier plate as well as preparation and application of BT resin-based composite dielectric material

By filling the BT resin/glass fiber cloth composite substrate with a "zero value effect", the problem of high thermal expansion coefficient of the BT resin-based chip packaging loading plate is solved, and the combination of low thermal expansion coefficient and excellent dielectric performance is achieved, meeting the application needs of IC chip packaging loading plates.

CN119613955AActive Publication Date: 2025-03-14LONGTENG ELECTRONICS TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411869032.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The linear thermal expansion coefficient of the existing BT resin-based chip packaging loading board is relatively high, which cannot meet the application needs of IC chip packaging loading boards.

Method used

The BT resin/glass fiber cloth composite substrate is used to fill with a mixed ceramic filler with a positive and negative thermal expansion coefficient with a "zero value effect". By modifying the thermal expansion coefficient of the ceramic filler to be 0, the thermal expansion coefficient of the composite material is reduced and the dielectric performance is improved.

Benefits of technology

The low thermal expansion coefficient (up to 4.3ppm/℃) and excellent dielectric properties of BT resin-based composite dielectric materials are achieved, meeting the performance requirements of IC chip packaging carrier boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613955A_ABST
    Figure CN119613955A_ABST
Patent Text Reader

Abstract

The invention discloses a BT resin-based composite dielectric material for an IC chip packaging substrate and preparation and application of the BT resin-based composite dielectric material. The BT resin-based composite dielectric material comprises a BT resin / glass fiber cloth composite base material and a mixed ceramic filler filled in the BT resin / glass fiber cloth composite base material, the thermal expansion coefficient of the mixed ceramic filler is 0; the BT resin / glass fabric base material is modified by using the positive and negative thermal expansion coefficient mixed ceramic filler with a zero value effect, so that the thermal expansion coefficient of the composite material can be reduced, and the dielectric property of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of circuit board materials, and in particular to a BT resin-based composite dielectric material for an IC chip packaging carrier board and the preparation and application thereof. Background Art

[0002] IC substrate is a key substrate developed on the basis of PCB related technologies. It is used to establish signal connection between IC chip and PCB. In addition, it can protect circuit, fix circuit and dissipate waste heat. With the rapid development of semiconductor technology, the integration requirements are getting higher and higher. As a result, the device size is constantly shrinking, which makes the number of devices per unit area increase and the circuit is becoming more and more complex. The copper clad laminate used for semiconductor packaging substrate has higher performance requirements: such as better dielectric properties, lower thermal expansion coefficient, etc., to improve the reliability of interconnection and installation. The main factor that determines the performance of copper clad laminate is the resin matrix material.

[0003] BT resin is a resin material developed by Mitsubishi Gas Chemical Company. It is synthesized from bismaleimide (BMI) and cyanate (CE). It has excellent heat resistance, low thermal expansion characteristics, excellent dielectric properties, etc. Although BT resin-based chip carriers have many excellent properties, domestic chip packaging manufacturers currently rely mainly on imports for BT resin-based chip carriers. The BT resin-based chip packaging carriers currently developed by domestic chip carrier manufacturers have a high linear thermal expansion coefficient, generally above 10ppm / ℃, which does not meet the application requirements of IC chip packaging carriers.

[0004] Therefore, it is necessary to provide a BT resin-based composite dielectric material and its process that has a good match with the linear thermal expansion coefficient of substrate silicon, a low linear thermal expansion coefficient, excellent dielectric properties and is suitable for large-scale production, so as to achieve domestic substitution of BT resin-based chip packaging carriers. Summary of the invention

[0005] In view of this, the present application provides a BT resin-based composite dielectric material for an IC chip packaging substrate and its preparation and application, which are used to solve the problem of how to improve the dielectric properties of the BT resin-based composite dielectric material while reducing the thermal expansion coefficient.

[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a BT resin-based composite dielectric material for an IC chip packaging carrier, comprising a BT resin / glass fiber cloth composite substrate and a mixed ceramic filler filled in the BT resin / glass fiber cloth composite substrate; the thermal expansion coefficient of the mixed ceramic filler is 0.

[0007] Preferably, the mixed ceramic filler includes the following components in mass proportions: 10-37 parts of modified positive thermal expansion coefficient ceramic filler and 10-37 parts of modified negative thermal expansion coefficient ceramic filler; the thermal expansion coefficient of the modified negative thermal expansion coefficient ceramic filler is -5ppm / ℃, and the thermal expansion coefficient of the modified positive thermal expansion coefficient ceramic filler is 2.2ppm / ℃.

[0008] Preferably, the modified positive thermal expansion coefficient ceramic filler is SiO modified by a silane coupling agent. 2 Ceramic powder, the modified negative thermal expansion coefficient ceramic filler is zirconium phosphotungstate ceramic powder modified by a silane coupling agent; and / or, the particle size of the modified negative thermal expansion coefficient ceramic filler is 1µm~3µm, and the particle size of the modified positive thermal expansion coefficient ceramic filler is 200~800nm.

[0009] Preferably, the preparation method of the modified positive thermal expansion coefficient ceramic filler is: immersing the dried positive thermal expansion coefficient ceramic filler in anhydrous ethanol, then dripping the modifier and ultrasonically washing, and after drying, the modified positive thermal expansion coefficient ceramic filler is obtained; and / or, the preparation method of the modified negative thermal expansion coefficient ceramic filler is: immersing the dried negative thermal expansion coefficient ceramic filler in anhydrous ethanol, then dripping the modifier and ultrasonically washing, and after drying, the modified negative thermal expansion coefficient ceramic filler is obtained.

[0010] Preferably, the modifier includes a silane coupling agent; the amount of the modifier is 1-2 wt% of the ceramic filler with a positive thermal expansion coefficient; the amount of the modifier is 1-2 wt% of the ceramic filler with a negative thermal expansion coefficient.

[0011] Preferably, the preparation method of BT resin is: using 4,4'-bismaleimidodiphenylmethane and bisphenol A cyanate as raw materials, 2,2'-diallylbisphenol A as a modifier, and N-methylpyrrolidone as a reaction solvent, to carry out polymerization reaction to obtain BT resin.

[0012] Preferably, the thickness of the glass fiber cloth is 0.030±0.010 mm, the tensile modulus of the glass fiber cloth is 67-70 GPa, the dielectric constant is 4.62-4.81@10 GHz, and the dielectric loss is 0.003-0.005@10 GHz.

[0013] In a second aspect, the present application provides a method for preparing a BT resin-based composite dielectric material for an IC chip packaging substrate, comprising the following steps: S1. After mixing the raw materials of the mixed ceramic filler and BT resin with an organic solvent in parts by mass, a mixed solution is obtained; S2. The mixed liquid is coated on the glass fiber cloth, and after hot pressing and curing, a BT resin-based composite dielectric material for IC chip packaging substrate is obtained.

[0014] Preferably, in step S1, 29-30 parts by mass of 4,4'-bismaleimidodiphenylmethane, 23-24 parts by mass of bisphenol A type cyanate, 20-25 parts by mass of 2,2'-diallyl bisphenol A, 10-35 parts by mass of modified positive thermal expansion coefficient ceramic filler, and 10-35 parts by mass of modified negative thermal expansion coefficient ceramic filler are mixed to obtain a mixed solution; in step S2, the amount of glass fiber cloth used is 45-50 parts by mass.

[0015] In a third aspect, the present application provides an application of a BT resin-based composite dielectric material for an IC chip packaging carrier in the field of circuit board materials.

[0016] The beneficial effects of the present application are as follows: the present application uses a mixed ceramic filler with positive and negative thermal expansion coefficients having a "zero value effect" to modify the BT resin / glass fiber cloth substrate, which can not only reduce the thermal expansion coefficient of the composite material, but also improve the dielectric properties of the composite material; the BT resin-based composite dielectric material prepared by the present application has a continuously adjustable dielectric constant (3.3-4.2), a dielectric loss between 0.004-0.0086, and a thermal expansion coefficient as low as 4.3ppm / ℃; The present application uses 4,4'-bismaleimidodiphenylmethane and bisphenol A cyanate as raw materials to prepare BT resin, which is beneficial to improving the dielectric properties of BT resin and reducing the thermal expansion coefficient of BT resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of the low dielectric loss microwave composite dielectric material for circuit boards prepared in Comparative Example 6; Figure 2 This is a scanning electron microscope image of the composite dielectric material prepared in Comparative Example 2; Figure 3 This is a scanning electron microscope image of the composite dielectric material prepared in Comparative Example 4; Figure 4 This is a scanning electron microscope image of the composite dielectric material prepared in Example 1. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0019] The present application provides a BT resin-based composite dielectric material for an IC chip packaging carrier, comprising a BT resin / glass fiber cloth composite substrate and a mixed ceramic filler filled in the BT resin / glass fiber cloth composite substrate; the thermal expansion coefficient of the mixed ceramic filler is 0.

[0020] The dielectric constant of the BT resin-based composite dielectric material for the IC chip packaging substrate of the present application is 3.3-4.2 and is continuously adjustable, the dielectric loss is between 0.004-0.0086, and the thermal expansion coefficient is 4-5ppm / °C.

[0021] In the present application, the reduction of the thermal expansion coefficient of the composite material is due to the combined effect of the negative thermal expansion coefficient ceramic filler, nano-silicon dioxide ceramic filler, compound filler and glass fiber cloth, and the improvement of the dielectric properties is also due to the combined effect of the negative thermal expansion coefficient ceramic filler, silicon dioxide ceramic filler and glass fiber cloth.

[0022] In some embodiments, the mixed ceramic filler includes the following components in mass proportions: 10-35 parts of modified positive thermal expansion coefficient ceramic filler and 10-35 parts of modified negative thermal expansion coefficient ceramic filler; in some embodiments, the thermal expansion coefficient of the modified negative thermal expansion coefficient ceramic filler is -5ppm / ℃, and the thermal expansion coefficient of the modified positive thermal expansion coefficient ceramic filler is 2.2ppm / ℃.

[0023] In some embodiments, the mass ratio of the BT resin / glass fiber cloth composite substrate to the mixed ceramic filler is 80-150:30-60.

[0024] In some embodiments, the modified positive thermal expansion coefficient ceramic filler is SiO modified by a silane coupling agent. 2 Ceramic powder, the modified negative thermal expansion coefficient ceramic filler is zirconium phosphotungstate ceramic powder modified by a silane coupling agent; and / or, the particle size of the modified negative thermal expansion coefficient ceramic filler is 1µm~3µm, the particle size of the modified positive thermal expansion coefficient ceramic filler is 200~800nm, and the purity of the positive thermal expansion coefficient ceramic filler is ≥99.9%.

[0025] In some embodiments, the preparation method of zirconium phosphotungstate ceramic powder is a solid phase sintering method, and the specific preparation method is as follows: Weigh zirconium dioxide ZrO in a molar ratio of 2:1:2 2 、Tungsten Oxide WO 3 、Ammonium dihydrogen phosphate NH 4 H 2 PO 4 Powder, mix the weighed powders and put them into a planetary ball mill and add deionized water to make the powders evenly immersed in a suspended state, then ball mill for 6 hours. After the ball milling is completed, place the mixed powders in a blast drying oven and set it to 80°C for 2 hours; The mixed powder was placed in a high-temperature muffle furnace for sintering. The sintering program was set to 5°C / min from room temperature to 1200°C and keep warm for 4 hours. After cooling in the furnace, an off-white solid solution was obtained. The sintered product powder was ball-milled for a second time for 12 hours to obtain zirconium phosphotungstate ceramic powder with uniform particle size.

[0026] In some embodiments, the preparation method of the modified positive thermal expansion coefficient ceramic filler is: immersing the dry positive thermal expansion coefficient ceramic filler in anhydrous ethanol, and then dripping the modifier and ultrasonically washing, washing and drying to obtain the modified positive thermal expansion coefficient ceramic filler; and / or, the preparation method of the modified negative thermal expansion coefficient ceramic filler is: immersing the dry negative thermal expansion coefficient ceramic filler in anhydrous ethanol, and then dripping the modifier and ultrasonically washing, washing and drying to obtain the modified negative thermal expansion coefficient ceramic filler.

[0027] In some embodiments, the modifier includes a silane coupling agent, such as KH550; the amount of the modifier is 1-2 wt % of the positive thermal expansion coefficient ceramic filler; the amount of the modifier is 1-2 wt % of the negative thermal expansion coefficient ceramic filler.

[0028] In some embodiments, the preparation method of the modified positive / negative thermal expansion coefficient ceramic filler is as follows: 1-2 wt% of the unmodified ceramic filler is weighed and dissolved in anhydrous ethanol, the mass ratio of the silane coupling agent to the anhydrous ethanol is 1:10, and then deionized water is added in a mass ratio of 1:4 to the silane coupling agent, and then ultrasonicated for 5 minutes to prepare a coupling agent solution; Take the unmodified ceramic filler and dry it at 120°C for 2 hours, then add it into anhydrous ethanol to completely immerse it, then add the coupling agent solution dropwise and ultrasonicate for 30 minutes. After mixing evenly, use anhydrous ethanol to wash away the unreacted silane coupling agent on the surface of the inorganic filler, and place the modified inorganic filler at 120°C to dry completely for use.

[0029] In some embodiments, the amount of the unmodified ceramic filler is 11-37 parts by weight, and the amount of the surface modifier is 0.1-0.2 parts by weight.

[0030] In some embodiments, the preparation method of BT resin is: using 4,4'-bismaleimidodiphenylmethane and bisphenol A cyanate as raw materials, 2,2'-diallylbisphenol A as a modifier, and N-methylpyrrolidone as a reaction solvent, and performing a polymerization reaction to obtain BT resin.

[0031] In some embodiments, the glass fiber cloth has a thickness of 0.030±0.010 mm, a tensile modulus of 67-70 GPa, a dielectric constant of 4.62-4.81@10 GHz, and a dielectric loss of 0.003-0.005@10 GHz.

[0032] In the present application, the glass fiber cloth has a negative effect on the thermal expansion performance of the composite material. The axial linear expansion coefficient of the glass fiber is small. As the temperature rises, the amplitude of the particle vibration in the glass fiber increases, and the average distance between atoms changes, which affects the linear thermal expansion coefficient of the composite BT resin-based material.

[0033] The present application provides a method for preparing a BT resin-based composite dielectric material for an IC chip packaging substrate, comprising the following steps: S1. After mixing the raw materials of the mixed ceramic filler and BT resin with an organic solvent in parts by mass, a mixed solution is obtained; S2. The mixed liquid is coated on the glass fiber cloth, and after hot pressing and curing, a BT resin-based composite dielectric material for IC chip packaging substrate is obtained.

[0034] In some embodiments, in step S1, 29-30 parts by mass of 4,4'-bismaleimidodiphenylmethane, 23-24 parts by mass of bisphenol A type cyanate, 20-25 parts by mass of 2,2'-diallyl bisphenol A, 11-37 parts by mass of modified positive thermal expansion coefficient ceramic filler, and 11-37 parts by mass of modified negative thermal expansion coefficient ceramic filler are mixed to obtain a mixed solution; in step S2, the amount of glass fiber cloth used is 45-50 parts by mass.

[0035] In some embodiments, in step S1, the mixing temperature is 130-150°C.

[0036] In some embodiments, in step S2, the hot pressing temperature curve of hot pressing curing is 150-250°C / 6h, and the pressure of hot pressing curing is 1-2Mpa.

[0037] The present application provides an application of a BT resin-based composite dielectric material for an IC chip packaging substrate in the field of circuit board materials.

[0038] The present solution is further described below through specific embodiments.

[0039] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0040] Source of raw materials Glass fiber cloth: purchased from Taishan Fiberglass Company, the tensile modulus of the glass fiber cloth is 67Gpa, the dielectric constant is 4.62@10GHz, the dielectric loss is 0.003@10GHz, and the thickness of the glass fiber cloth is 0.030±0.010mm; Modified negative thermal expansion coefficient ceramic filler: weigh silane coupling agent KH550 according to 1.5% of the amount of zirconium phosphotungstate, dissolve it in anhydrous ethanol, the mass ratio of silane coupling agent to anhydrous ethanol is 1:10, then add deionized water with a mass ratio of 1:4 to silane coupling agent, and then ultrasonicate for 5 minutes to prepare a coupling agent solution; take zirconium phosphotungstate with an average particle size of 1µm, dry it at 120℃ for 2 hours, add it to anhydrous ethanol to make it completely immersed, then drop the coupling agent solution and ultrasonicate for 30 minutes, mix it evenly, and use anhydrous ethanol to wash off the unreacted silane coupling agent on the surface of zirconium phosphotungstate, and place the modified zirconium phosphotungstate at 120℃ to dry it completely for use. It has been identified that the thermal expansion coefficient of the modified negative thermal expansion coefficient ceramic filler is -5ppm / ℃.

[0041] Modified positive thermal expansion coefficient ceramic filler: weigh silane coupling agent KH550 according to 2.0% of the amount of silica and dissolve it in anhydrous ethanol, the mass ratio of silane coupling agent to anhydrous ethanol is 1:10, then add deionized water with a mass ratio of 1:4 to the silane coupling agent and ultrasonicate for 5 minutes to prepare a coupling agent solution; take silica with an average particle size of 500nm, place it at 120℃ and dry it for 2 hours, then add it to anhydrous ethanol to make it completely immersed, then drop the coupling agent solution and ultrasonicate for 30 minutes, mix it evenly, use anhydrous ethanol to wash off the unreacted silane coupling agent on the surface of silica, and place the modified silica at 120℃ to dry it completely for use. It has been identified that the thermal expansion coefficient of the modified positive thermal expansion coefficient ceramic filler is 2.2ppm / ℃.

[0042] 4,4'-Bismaleimidodiphenylmethane and 2,2'-diallylbisphenol A were purchased from Wuhan Zhisheng Technology; bisphenol A cyanate was purchased from Yangzhou Tianqi New Materials Co., Ltd.

[0043] Example 1 A BT resin-based composite dielectric material for an IC chip packaging carrier comprises a BT resin / glass fiber cloth composite substrate and a mixed ceramic filler filled in the BT resin / glass fiber cloth composite substrate; the thermal expansion coefficient of the mixed ceramic filler is 0; the mixed ceramic filler comprises a modified positive thermal expansion coefficient ceramic filler and a modified negative thermal expansion coefficient ceramic filler.

[0044] The preparation method of BT resin-based composite dielectric material for IC chip packaging substrate is as follows: S1. Add 29.83 parts of 4,4'-bismaleimidodiphenylmethane, 23.17 parts of bisphenol A cyanate, 20 parts of 2,2'-diallylbisphenol A, 26 parts of modified positive thermal expansion coefficient ceramic filler, 11 parts of modified negative thermal expansion coefficient ceramic filler and organic solvent N-methylpyrrolidone into a magnetic stirrer, stir at 130°C for 30 minutes, and after the mixture is fully mixed, obtain a mixed solution; S2. The mixed liquid is coated on 47 parts of glass fiber cloth, dried at 150°C, and then cured by hot pressing in a vulcanizer. The hot pressing temperature curve of the vulcanizer is 250°C / 6h, and the hot pressing pressure is 1MPa, thereby obtaining a BT resin-based composite dielectric material for IC chip packaging substrates.

[0045] Comparative Example 1 A BT resin-based composite dielectric material for an IC chip packaging carrier comprises a BT resin / glass fiber cloth composite substrate and a mixed ceramic filler filled in the BT resin / glass fiber cloth composite substrate; the mixed ceramic filler comprises a modified positive thermal expansion coefficient ceramic filler and a modified negative thermal expansion coefficient ceramic filler.

[0046] The preparation method of BT resin-based composite dielectric material for IC chip packaging substrate is as follows: S1. Add 29.83 parts of 4,4'-bismaleimidodiphenylmethane, 23.17 parts of bisphenol A cyanate, 20 parts of 2,2'-diallylbisphenol A, 11 parts of modified positive thermal expansion coefficient ceramic filler, 26 parts of modified negative thermal expansion coefficient ceramic filler and organic solvent N-methylpyrrolidone into a magnetic stirrer, stir at 130°C for 30 minutes, and after the mixture is fully mixed, obtain a mixed solution; S2. The mixed liquid is coated on 47 parts of glass fiber cloth, dried at 150°C, and then cured by hot pressing in a vulcanizer. The hot pressing temperature curve of the vulcanizer is 250°C / 6h, and the hot pressing pressure is 1MPa, thereby obtaining a BT resin-based composite dielectric material for IC chip packaging substrates.

[0047] Comparative Example 2 A BT resin-based composite dielectric material for an IC chip packaging carrier comprises a BT resin / glass fiber cloth composite substrate and a modified positive thermal expansion coefficient ceramic filler filled in the BT resin / glass fiber cloth composite substrate.

[0048] The preparation method of BT resin-based composite dielectric material for IC chip packaging substrate is as follows: S1. 29.83 parts of 4,4'-bismaleimidodiphenylmethane, 23.17 parts of bisphenol A cyanate, 20 parts of 2,2'-diallyl bisphenol A, 26 parts of modified positive thermal expansion coefficient ceramic filler and organic solvent N-methylpyrrolidone were added into a magnetic stirrer and stirred at 130°C for 30 minutes. After the mixture was fully mixed, a mixed solution was obtained; S2. The mixed liquid is coated on 47 parts of glass fiber cloth, dried at 150°C, and then cured by hot pressing in a vulcanizer. The hot pressing temperature curve of the vulcanizer is 250°C / 6h, and the hot pressing pressure is 1MPa, thereby obtaining a BT resin-based composite dielectric material for IC chip packaging substrates.

[0049] Comparative Example 3 A BT resin-based composite dielectric material for an IC chip packaging substrate, the other contents of which are the same as those of comparative example 2, except that the amount of the modified positive thermal expansion coefficient ceramic filler is 37 parts.

[0050] Comparative Example 4 A BT resin-based composite dielectric material for an IC chip packaging carrier comprises a BT resin / glass fiber cloth composite substrate and a modified negative thermal expansion coefficient ceramic filler filled in the BT resin / glass fiber cloth composite substrate.

[0051] The preparation method of BT resin-based composite dielectric material for IC chip packaging substrate is as follows: S1. 29.83 parts of 4,4'-bismaleimidodiphenylmethane, 23.17 parts of bisphenol A cyanate, 20 parts of 2,2'-diallyl bisphenol A, 11 parts of modified negative thermal expansion coefficient ceramic filler and organic solvent N-methylpyrrolidone were added into a magnetic stirrer and stirred at 130°C for 30 minutes. After the mixture was fully mixed, a mixed solution was obtained; S2. The mixed liquid is coated on 47 parts of glass fiber cloth, dried at 150°C, and then cured by hot pressing in a vulcanizer. The hot pressing temperature curve of the vulcanizer is 250°C / 6h, and the hot pressing pressure is 1MPa, thereby obtaining a BT resin-based composite dielectric material for IC chip packaging substrates.

[0052] Comparative Example 5 A BT resin-based composite dielectric material for an IC chip packaging substrate, the other contents of which are the same as those of comparative example 4, except that the amount of the modified negative thermal expansion coefficient ceramic filler is 37 parts.

[0053] Comparative Example 6 A BT resin-based composite dielectric material for an IC chip packaging carrier comprises a BT resin / glass fiber cloth composite substrate.

[0054] The preparation method of BT resin-based composite dielectric material for IC chip packaging substrate is as follows: S1. Add 29.83 parts of 4,4'-bismaleimidodiphenylmethane, 23.17 parts of bisphenol A cyanate, 20 parts of 2,2'-diallyl bisphenol A and organic solvent N-methylpyrrolidone into a magnetic stirrer, stir at 130°C for 30 minutes, and after the mixture is fully mixed, obtain a mixed solution; S2. The mixed liquid is coated on 47 parts of glass fiber cloth, dried at 150°C, and then cured by hot pressing in a vulcanizer. The hot pressing temperature curve of the vulcanizer is 250°C / 6h, and the hot pressing pressure is 1MPa, thereby obtaining a BT resin-based composite dielectric material for IC chip packaging substrates.

[0055] Test and Evaluation The composite dielectric materials obtained in Comparative Example 2, Comparative Example 4, Comparative Example 6, and Example 1 were scanned by electron microscope. Among them, the circuit board prepared in Comparative Example 6 was scanned by a scanning electron microscope using a low dielectric loss microwave composite dielectric material. Figure 1 As shown; the scanning electron microscope of the composite dielectric material prepared in Comparative Example 2, as Figure 2 As shown; the scanning electron microscope of the composite dielectric material prepared in Comparative Example 4, as Figure 3 As shown; the scanning electron microscope of the composite dielectric material prepared in Example 1, as Figure 4 As shown. Figure 1-4 From the scanning electron microscope image, it can be seen that the glass fiber cloth is relatively intact inside the composite material, without obvious signs of fragmentation, indicating that the interface compatibility between the glass fiber cloth and the BT resin is good, the particle size of the ceramic filler is relatively small, and the modified ceramic filler has good compatibility with the BT resin matrix.

[0056] The following performance tests were conducted on the BT resin-based composite dielectric material (modified PP / PPO / GF-based composite dielectric material) for IC chip packaging carrier prepared in the above examples and comparative examples: The dielectric properties were tested using the Split Dielectric Resonator (SPDR) method.

[0057] The thermal expansion coefficient is tested according to ISO11359-2 plastic thermodynamic analysis method for the heat deformation temperature of the sample, and the measurement temperature range is from room temperature to 200°C.

[0058] The results are shown in Table 1.

[0059] Table 1 Performance test results of various materials

[0060] Comparative Examples 2 and 3 use different contents of modified silica filler to modify the BT resin / glass fiber cloth composite substrate, Comparative Examples 4 and 5 use different contents of modified zirconium phosphotungstate filler to modify the BT resin / glass fiber cloth composite substrate, and Example 1 and Comparative Example 1 use modified silica and modified zirconium phosphotungstate mixed filler with different compounding ratios to modify the BT resin / glass fiber cloth composite substrate, but the thermal expansion coefficient of the modified silica and modified zirconium phosphotungstate mixed filler of Comparative Example 1 is not 0, while the thermal expansion coefficient of the modified silica and modified zirconium phosphotungstate mixed filler of Example 1 is 0.

[0061] From the experimental results in Table 1, it can be seen that the linear thermal expansion coefficient of the BT resin / glass fiber cloth composite substrate modified by modified silica is between 12 and 14 ppm / ℃, and the thermal expansion coefficient of the modified silica is 2.2 ppm / ℃, which has a negative effect on the thermal expansion performance of the composite material, but the thermal expansion coefficient is still relatively high and cannot meet the application requirements of the IC chip packaging substrate; the linear thermal expansion coefficient of the BT resin / glass fiber cloth composite substrate modified by modified zirconium tungstate phosphotungstate is reduced to 7.4 ppm / ℃, which is 49% lower than that of the unmodified BT resin / glass fiber cloth composite substrate of Comparative Example 6, and the thermal expansion coefficient is reduced by 40% relative to the use of modified silica filler alone (Comparative Example 2) at the same filling ratio. Example 1 and Comparative Example 1 use modified silica and modified zirconium phosphotungstate mixed filler to modify the BT resin / glass fiber cloth-based composite substrate, and the linear thermal expansion coefficient is 4~5 ppm / ℃. From the results of Example 1, Comparative Example 3 and Comparative Example 5, it can be seen that under the same addition ratio, the thermal expansion coefficient of the composite material prepared by using a mixed ceramic filler with a "zero value effect" can greatly reduce the thermal expansion coefficient of the composite substrate compared to a single positive / negative thermal expansion coefficient filler, and is relatively close to the linear thermal expansion coefficient of the chip substrate silicon wafer, and can better match the thermal expansion performance with the substrate silicon.

[0062] The mixed filler of the present application is more excellent in improving the thermal expansion performance of the composite material, and can significantly reduce the thermal expansion coefficient when the content of negative thermal expansion ceramic filler is small. Since the cost of silicon dioxide is low, while the cost of zirconium phosphotungstate is high and the preparation method is relatively cumbersome, the method of mixed filler modification has extremely high economic benefits. The above experimental results show that the present invention comprehensively uses modification means to improve the dielectric properties, linear thermal expansion coefficient, etc. of BT resin-based composite materials, so that the obtained extremely low thermal expansion coefficient BT resin-based composite dielectric substrate can be used in IC chip packaging.

[0063] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A BT resin-based composite dielectric material for IC chip packaging substrate, characterized in that: It comprises a BT resin / glass fiber cloth composite substrate and a mixed ceramic filler filled in the BT resin / glass fiber cloth composite substrate; the thermal expansion coefficient of the mixed ceramic filler is 0.

2. The BT resin-based composite dielectric material for IC chip packaging substrate according to claim 1, characterized in that: The mixed ceramic filler comprises the following components in mass proportions: 11-37 parts of a modified positive thermal expansion coefficient ceramic filler and 11-37 parts of a modified negative thermal expansion coefficient ceramic filler; and / or, The thermal expansion coefficient of the modified negative thermal expansion coefficient ceramic filler is -3ppm / °C to -5ppm / °C, and the thermal expansion coefficient of the modified positive thermal expansion coefficient ceramic filler is 2.2ppm / °C to 2.6ppm / °C.

3. The BT resin-based composite dielectric material for IC chip packaging substrate according to claim 2, characterized in that: The modified positive thermal expansion coefficient ceramic filler is SiO2 ceramic powder modified by a silane coupling agent, and the modified negative thermal expansion coefficient ceramic filler is zirconium phosphotungstate ceramic powder modified by a silane coupling agent; and / or, The particle size of the modified negative thermal expansion coefficient ceramic filler is 1µm-3µm, and the particle size of the modified positive thermal expansion coefficient ceramic filler is 200-800nm.

4. The BT resin-based composite dielectric material for IC chip packaging substrate according to claim 2, characterized in that: The preparation method of the modified positive thermal expansion coefficient ceramic filler is: immersing the dried positive thermal expansion coefficient ceramic filler in anhydrous ethanol, then dripping a modifier and ultrasonically treating it, washing it, and drying it to obtain the modified positive thermal expansion coefficient ceramic filler; and / or, The preparation method of the modified negative thermal expansion coefficient ceramic filler is as follows: the dried negative thermal expansion coefficient ceramic filler is immersed in anhydrous ethanol, and then a modifier is dropped into the ceramic filler for ultrasonic treatment, and the modified negative thermal expansion coefficient ceramic filler is obtained after washing and drying.

5. The BT resin-based composite dielectric material for IC chip packaging substrate according to claim 4, characterized in that: The modifier includes a silane coupling agent; the amount of the modifier is 1-2wt% of the positive thermal expansion coefficient ceramic filler; the amount of the modifier is 1-2wt% of the negative thermal expansion coefficient ceramic filler.

6. The BT resin-based composite dielectric material for IC chip packaging substrate according to claim 1, characterized in that: The preparation method of the BT resin is as follows: using 4,4'-bismaleimidodiphenylmethane and bisphenol A type cyanate as raw materials, 2,2'-diallylbisphenol A as a modifier, and N-methylpyrrolidone as a reaction solvent to carry out a polymerization reaction to obtain the BT resin.

7. The BT resin-based composite dielectric material for IC chip packaging substrate according to claim 1, characterized in that: The thickness of the glass fiber cloth is 0.030±0.010 mm, the tensile modulus of the glass fiber cloth is 67-70 GPa, the dielectric constant is 4.62-4.81@10 GHz, and the dielectric loss is 0.003-0.005@10 GHz.

8. A method for preparing the BT resin-based composite dielectric material for IC chip packaging carrier according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. After mixing the raw materials of the mixed ceramic filler and BT resin with an organic solvent in parts by mass, a mixed solution is obtained; S2. The mixed liquid is coated on the glass fiber cloth, and after hot pressing and curing, the BT resin-based composite dielectric material for the IC chip packaging carrier is obtained.

9. The preparation method according to claim 8, characterized in that: In step S1, 29-30 parts by mass of 4,4'-bismaleimidodiphenylmethane, 23-24 parts by mass of bisphenol A type cyanate, 20-25 parts by mass of 2,2'-diallylbisphenol A, 11-37 parts by mass of modified positive thermal expansion coefficient ceramic filler, and 11-37 parts by mass of modified negative thermal expansion coefficient ceramic filler are mixed to obtain a mixed solution; in step S2, the amount of the glass fiber cloth used is 45-50 parts by mass.

10. Application of the BT resin-based composite dielectric material for IC chip packaging carrier obtained by the preparation method according to any one of claims 8 to 9 in the field of circuit board materials.

Citation Information

Patent Citations

  • Modified bismaleimide-triazine resin and preparation method thereof

    CN101824147A

  • Composite material for substrate containing inorganic filling material and liquid crystal thermosetting oligomer with negative thermal expansion coefficient

    CN102115597A

  • Filler for resin composition, filler-containing slurry composition, filler-containing resin composition, and method for producing filler for resin composition

    CN110573562A

  • Preparation method and application of resin composition

    CN117736579A

  • Polyolefin-based composite substrate with near-zero dielectric constant temperature coefficient and preparation method of polyolefin-based composite substrate

    CN118185145A